ISAR-SAFE: No Difference in 6-Month vs 12-Month DAPT after DES - Cunningham, Muriel (MD Conference Express, 2014)
Current treatment guidelines recommend that patients undergoing drug-eluting stent percutaneous coronary intervention take dual antiplatelet therapy (DAPT) consisting of aspirin plus an adenosine diphosphate receptor inhibitor for at least 12 months after the procedure. The Safety and Efficacy of Six Months Dual Antiplatelet Therapy After Drug-Eluting Stenting [ISAR-SAFE] trial was designed to determine whether 6 months of DAPT treatment was non-inferior to 12 months, as discussed in this article.